Pan-arthropod analysis reveals somatic piRNAs as an ancestral defence against transposable elements. Issue 1 (January 2018) - Lewis, Samuel; Quarles, Kaycee; Yang, Yujing; Tanguy, Melanie; Frézal, Lise; Smith, Stephen; Sharma, Prashant; Cordaux, Richard; Gilbert, Clément; Giraud, Isabelle; Collins, David; Zamore, Phillip; et al.
Abstract In animals, small RNA molecules termed PIWI-interacting RNAs (piRNAs) silence transposable elements (TEs), protecting the germline from genomic instability and mutation. piRNAs have been detected in the soma in a few animals, but these are believed to be specific adaptations of individual species. Here, we report that somatic piRNAs were probably present in the ancestral arthropod more than 500 million years ago. Analysis of 20 species across the arthropod phylum suggests that somatic piRNAs targeting TEs and messenger RNAs are common among arthropods. The presence of an RNA-dependent RNA polymerase in chelicerates (horseshoe crabs, spiders and scorpions) suggests that arthropods originally used a plant-like RNA interference mechanism to silence TEs. Our results call into question the view that the ancestral role of the piRNA pathway was to protect the germline and demonstrate that small RNA silencing pathways have been repurposed for both somatic and germline functions throughout arthropod evolution. The widespread presence of somatic PIWI-interacting RNAs targeting transposable elements across the arthropod phylum suggests that this pathway was active in the last common ancestor of arthropods.